P96 Limitations of Internet searching for understanding the commissioning and delivery of health services: findings from a systematic review of diagnostic ultrasound services. (13th September 2016) - Chambers, D; Booth, A; Baxter, SK; Johnson, M; Goyder, E
Abstract : Background: Diagnostic ultrasound services are commonly provided by direct access to hospital-based facilities for GPs. Services may also be delivered in primary care or community settings, for example by appropriately trained GPs or mobile services. As part of a larger project, we used an Internet and grey literature search to identify current providers and models of service in the UK NHS (primarily England). Methods: Internet searches were performed using the Google search engine. We also searched OpenGrey (European grey literature database) and the website of the National Institute for Health Research (NIHR) Diagnostic Evidence Co-Operative (DEC) Oxford, which specialises in diagnostic tests suitable for use in primary care. The first 100 results from Google searches were examined. Websites of companies providing diagnostic ultrasound services in NHS community settings and of 'NHS community diagnostic centres' (providing diagnostic ultrasound alongside other tests) were searched for evaluations or fuller descriptions of the services and any information on governance, accreditation and similar issues. Results: We identified details of 22 companies providing diagnostic ultrasound services, one of which appeared to be an exclusively private service. Details available on the company websites were highly variable. Commonly reported features included time standards for appointments and report delivery and patient satisfaction ratings. Links to the NHS were emphasised by most of the companies. It appeared that many staff worked part-time for the companies and the remainder of the time for NHS organisations. Services were generally commissioned through the 'any qualified provider' (AQP) system. All the services appeared to follow the model of a mobile service operating through GP surgeries and other community sites. Services were staffed by radiographers (and healthcare assistants) with access to consultant radiologists as required. We also identified websites for four 'community diagnostic centres' and five 'primary care centres' (diagnostic services integrated with GP surgeries). We did not identify any listings of what types of services are being commissioned and by whom or any reports of evaluations of services. Conclusion: Community-based services run by non-NHS providers with links to the NHS for governance and quality control are common. However, our findings should be regarded as a snapshot rather than a comprehensive list. At present it appears difficult to compile information about service delivery and evaluation from Internet sources. There is an urgent need for more comprehensive information to support commissioning decisions and inform the public.